Pengaruh Karakteristik Teknologi dan Karakteristik Pekerjaan terhadap Penerapan “Collaboration Technology Internet Content Filter” - Sulistyarini, Dhanik (FIkom Unisba, 2005)
The purpose of this research was to empirically examine the influence of technology characteristics and task characteristics on the implementation of collaboration technology which is internet content filter. Data were collected using questionnaires. The respondents of this research were 15-19 years old teenagers in Bandar Lampung, which were 100 respondents. The research was conducted at Kecamatan Kedaton, Bandar Lampung. The results showed that among the two independent variables, task characteristics variable was the dominant variable in influencing the respondents to implement the collaboration technology internet content filter with the value of r partial of 0,317 with t hit=3,289 and p=0,001, since it had the biggest regression coefficient.